Білім беруде Кембридж тəсілдерін қолданудың тиімділігі - Жайлаубаева, И.Ж (My University, 2016)
he actual value of the given article reflects the modern necessity of up-dating the system of Kazakhstani education using a new structure and content of the lesson material. The question under consideration in the article is to investigate new methods and techniques in teaching gifted students, e.g. Vienne diagram, 5 line poems and others. The observed techniques and strategies are crucial for developing students’ critical thinking abilities, to increase the efficiency of the lesson in general.
Keywords: differentiated teaching; Cambridge techniques; leadership in education; working with gifted students